Analise comparativa entre laje nervurada em concreto armado protendido - Fernando, Natalia Siqueira Ortiz (2019)
The purpose of this work is to compare ribbed slabs in reinforced and prestressed concrete, evaluating items such as economy, execution, performance, advantages and disadvantages in their use. It was not intended to deepen the structural analysis, nor to cover large areas case studies. First, a brief history and analysis of the ribbed slabs in general is shown, followed by a presentation on reinforced and prestressed concrete, based on bibliographies in which articles, tables, specialized companies, books and classes on such materials were analyzed. After this analysis, a study was carried out among some companies specialized in this technology, which showed current market data and productivity indexes, where it was possible to realize the advantage of the use of prestressing on reinforced concrete, proving a great reduction in the execution time. and mainly in the consumption of materials, bringing economic benefits both in the purchase of materials and labor.